(untitled) (Bangabandhu Sheikh Mujib Medical University Journal, 2016)
Carcinoma occurring in the cutaneous lesions of Lichen Planus though rarely mentioned in literature does occw-and should be kept in mind while treating such lesions. We report a 30 year female who developed a squamous cell carcinoma in a long standing hypertropic lichen planus in the lower leg. This case is being presented to indicate the possibility of malignant transformation of cutaneous lichen planus to carcinoma, especially in the hypertrophic fonns and the need to have an early diagnosis so that it can be treated in the initial stages. A high degree of suspicion should be present whenever we come across a non healing lesion in a patient with lichen planus. A few markers, which may give us a clue for increased chances of malignant transformation in these cases is presented.